The feed values of indigenous multipurpose trees for sheep in Ethiopia: The case of Vernonia amygdalina, Buddleja polystachya and Maesa lanceolata - Haile, Aynalem; Tolemariam, T. (2008)
The feed resources base, the feeding systems and feed values of three indigenous trees Girawa, Anfare and Kelewa (Local (Amharic), Ethiopian names ) were studied for sheep in sub humid, mid altitude area of south western Ethiopia. The study involved a survey of the feed resources base and assessment of the feeding systems, chemical analysis and in vitro dry matter digestibility. In addition, Girawa was selected to study its effect on growth performances using 32 lambs. The levels of Girawa used for the growth performance study in groups I, II, III and IV, respectively were 100 g/d, 200 g/d, 300 g/d and 400 g/d. The main feed resources for sheep in Jimma area were found to be natural pasture, crop residues, crop aftermaths and indigenous multipurpose trees. Grazing on natural pasture constituted the main feeding system. The indigenous trees were cut and fed occasionally. The levels of CP ranged from 186.2 to 244.4 g/kg DM with minimum level in Anfare. Higher values were recorded for Girawa. Organic matter content was higher for Anfare (924.3 g/kg DM) and lower for Girawa (877.9 g/kg DM). In vitro dry matter digestibility values were 0.448, 0.422 and 0.458 for Girawa, Anfare and Kelewa, respectively. Supplementation of Girawa had an effect (p<0.01) on live weight gains of lambs. Lambs that were offered 400 g/d of Girawa had a higher daily live weight gain (95.1 g/d) compared to those supplemented with 200 (43.3 g/d) and 300 g/d (50.5 g/d) of Girawa as well as the control group (34.0 g/d). Weight gains were not different between the control group and those supplemented with 200 and 300 g/d of Girawa. It was concluded that these feed resources represent a great potential for sheep production in areas where the resources are available. It is also suggested that more studies are needed on higher level of Girawa than the present study on animal performances along with its anti-nutritional effects.